Energy, exergy and sustainability assessments of a cogeneration system for ceramic industry. (25th May 2018) - Caglayan, Hasan; Caliskan, Hakan
Highlights: Novel cogeneration system is proposed for the dryer process in a ceramic industry. Energy, exergy and sustainability analyses are applied under various conditions. Cogeneration system provides 0.1115 m 3 /s natural gas saving for ground tile dryer. Cogeneration system provides 0.0732 m 3 /s natural gas saving for wall tile dryer. Abstract: In this study, energy, exergy and sustainability analyses are applied in the ceramic sector to simulate gas turbine based cogeneration plant model. The cogeneration system mainly consists of a proposed gas turbine unit, a wall tile dryer and a ground tile dryer. The energy analysis is performed, and then the exergy and sustainability analyses are applied for the five different dead state (environment) temperatures varying from 10 °C to 30 °C (interval of 5 °C). It is found that the most energy efficient components are determined as the air compressor and combustion chamber, while the minimum one is obtained to be wall tile dryer (7.98%). The maximum sustainability and exergy efficiency (89.46%) are determined for the air compressor as at 10 °C dead state temperature. The cogeneration (overall) system has 17.51% energy efficiency; while its maximum exergy efficiency is found to be 29.98% at 30 °C environment temperature. The sustainabilities of the components are also directly proportional to their exergy efficiencies. Furthermore, the utilization of the gas turbine unit included cogeneration system can provide 0.1115 m 3 /s and 0.0732 m 3 /s natural gas saving for the ground and wall tile dryers, respectively.